Electromechanical Properties of P(VDF-TrFE)/CNT and P(VDF-TrFE)/Gr Composites - Park, Youn Duk; Kang, Young Jong; Hong, Soon Man; Koo, Chong Min (TAYLOR & FRANCIS LTD, 2012)
Electromechanical properties of poly (vinylidenefluoride-co-trifluoroethylene) (P(VDFTrFE))/carbon nanotube (CNT), P(VDF-TrFE)/graphene (Gr) composites were investigated. The P(VDF-TrFE) composites with conductive fillers had the enhanced electromechanical strain response, which was affected by filler concentration but also by filler type. The strain was increased with the filler concentration. P(VDF-TrFE))/Gr composites had the higher strain response than the P(VDF-TrFE)/CNT composites at the same filler concentration level.